2009
DOI: 10.1590/s1806-37132009001000006
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de fumantes atendidos em serviço público para tratamento do tabagismo

Abstract: Smokers seeking assistance for smoking cessation were socially disadvantaged, presented a high degree of nicotine dependence and had previously made smoking-cessation attempts without the benefit of a structured program. Therefore, in order to be effective, smoking control interventions should take into consideration the general characteristics of the smokers treated via the public health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
0
7
0
17
Order By: Relevance
“…23 Regarding the "Professional Training" category, it is believed that the training of health professionals focused on minimizing the harms of tobacco use should be part of the construction of knowledge for their work. 14,18 One literature review corroborates these data on the effectiveness of pharmacological and psychosocial interventions for smoking cessation treatment, which emphasizes the involvement of an interdisciplinary team as essential to the success rate of smoking cessation. A review that examined the use of motivational interviewing, a therapeutic method that uses a different way to help people recognizing that they can do something about their present or potential problems, concluded that this approach does not bring significant results for smokers with high dependency.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…23 Regarding the "Professional Training" category, it is believed that the training of health professionals focused on minimizing the harms of tobacco use should be part of the construction of knowledge for their work. 14,18 One literature review corroborates these data on the effectiveness of pharmacological and psychosocial interventions for smoking cessation treatment, which emphasizes the involvement of an interdisciplinary team as essential to the success rate of smoking cessation. A review that examined the use of motivational interviewing, a therapeutic method that uses a different way to help people recognizing that they can do something about their present or potential problems, concluded that this approach does not bring significant results for smokers with high dependency.…”
mentioning
confidence: 78%
“…24 Out of the nine evaluated observational studies, six showed a prevalence of 62.8% of women. [15][16][17][18][19][20] The predominance of women seeking smoking cessation programs may be related to the difficulty to stop the habit without help and availability of time for attending the programs. 15,17 Historically, women seek health services more than men, either for care to family members or their own.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atenta-se para outro dado importante, o da relação inversa da prevalência tabágica com a renda familiar b em como para a escolaridade do idoso 28,29,30) . Os achados citados permitem inferir que apesar de ser uma adição democrática, que incide e prevalece em uma gama de contextos, independente da variável sociodemográfica que se avalia, o tabagismo prevalece mais intensamente nas camadas populares ou com baixa renda, numa dinâmica que contempla o comprometimento negativo de outros indicadores do estado geral de saúde, bem como de qualidade de vida.…”
Section: Tema 2 Tabagismo E Variáveis Sociodemográficas No Idosounclassified